Emerging Photovoltaics: Organic, Copper Zinc Tin Sulphide, and Perovskite-Based Solar Cells. (6th September 2016) - Rao, Shraavya; Morankar, Ankita; Verma, Himani; Goswami, Prerna
Abstract : As the photovoltaics industry continues to grow rapidly, materials other than silicon are being explored. The aim is to develop technologies that use environmentally friendly, abundant materials, low-cost manufacturing processes without compromising on efficiencies and lifetimes. This paper discusses three of the emerging technologies, organic, copper zinc tin sulphide (CZTS), and perovskite-based solar cells, their advantages, and the possible challenges in making these technologies commercially available.